INVESTIGATING THE ASSOCIATION BETWEEN RHO-KINASE 1 (ROCK1) GENE POLYMORPHISMS AND SYSTEMIC SCLEROSIS - Pehlivan, Y.; Oztuzcu, S.; Donmez, S.; Alibaz-Oner, F.; Cetin, G. Yildirim; Yolbas, S.; Onat, A. Mesut (Bmj Publishing Group, 2013)
[Abstract Not Available]